SIFAT LISTRIK SUPERKONDUKTOR YBa2Cu3O7-x HASIL PROSES PELELEHAN DENGAN DOPANT Ti[Electrical Characterictic of YBa2Cu3O7-x Superconductor Doped by Ti Using Melting Process] - Winatapura, Didin S; MP, Yustinus; A A, Wisnu; Deswita, Deswita; Sukirman, E (Jurnal Metalurgi, 2012)
ELECTRICAL CHARACTERICTIC OF YBa2Cu3O7-x SUPERCONDUCTOR DOPED BY Ti USING MELTING PROCESS. Synthesis of YBa2Cu3O7-x (YBCO) superconductor which is doped by Ti using modified melt-textured growth (MMTG) method has been done. The specimen was made by solid state reaction by adding Ti powder to precursor of YBCO result with composition variation (in weight %) of 0.4, 0.7, 1 and 1.3. The melt process of YBCO was done at 1100°C for 12 minutes then cooled rapidly to 1000°C followed by slow cooling to 960°C. Identification of the specimen phase was verified using x-rays diffraction (XRD) and followed by Rietveld method analysis. The critical temperature, Tc and current density, Jc were measured by means of four point probe (FPP). The microstructure and chemical composition of the specimen were observed using scanning electron microscope (SEM) and energy dispersive x-ray spectroscopy (EDS). The result shows that the specimen was YBa2Cu3O7-x high Tc superconductor of 123-phase having orthorhombic crystal structure of Pmmm no. 47 space group. The critical current density, Jc of the specimen was obtained about 67A.cm-2 and then decreased continuously with increasing of Ti dopant till Jc » 4A.cm-2. Decreasing of Jc caused by Ti can not prevent the growth of 211 phases. In increasing Ti content, 211 phases also increase with unhomogeneous distribution and continue to grow. There is also formation ofmicrocracks parallel to and crossing the YBCO grains. As a result, YBCO have smaller and shorter grain size compared to YBCO grain without Ti doping. Increasing of Ti content also cause decrease from 365 °C to 350 °C.